2020
DOI: 10.1021/acsami.0c00815
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Particle Spectroscopy for Detection of Influenza A Virus Subtype H1N1

Abstract: Magnetic nanoparticles (MNPs) with proper surface functionalization have been extensively applied as labels for magnetic immunoassays, carriers for controlled drug/gene delivery, tracers and contrasts for magnetic imaging, etc. Here, we introduce a new biosensing scheme based on magnetic particle spectroscopy (MPS) and the self-assembly of MNPs to quantitatively detect H1N1 nucleoprotein molecules. MPS monitors the harmonics of oscillating MNPs as a metric for the freedom of rotational process, thus indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 58 publications
0
79
0
Order By: Relevance
“… 44 In a MPS platform, external sinusoidal magnetic fields (also called excitation fields) are applied to periodically magnetize (and magnetically saturate) the MNPs, as shown in Figure 5 A1,A3. 85 87 , 95 101 The time-varying dipolar magnetic fields generated by MNPs as a response to the applied fields ( Figure 5 A2,A4) are monitored by pick-up coils. As a result of Faraday’s law of induction, the time-varying electric voltages from pick-up coils are recorded and MPS spectra are extracted for analysis, as shown in Figure 5 A3,A6).…”
Section: Mps Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“… 44 In a MPS platform, external sinusoidal magnetic fields (also called excitation fields) are applied to periodically magnetize (and magnetically saturate) the MNPs, as shown in Figure 5 A1,A3. 85 87 , 95 101 The time-varying dipolar magnetic fields generated by MNPs as a response to the applied fields ( Figure 5 A2,A4) are monitored by pick-up coils. As a result of Faraday’s law of induction, the time-varying electric voltages from pick-up coils are recorded and MPS spectra are extracted for analysis, as shown in Figure 5 A3,A6).…”
Section: Mps Platformsmentioning
confidence: 99%
“…Wu et al reported the volume-based MPS immunoassay platform utilizing the polyclonal-antibody-induced cross-linking of MNPs for one step, the wash-free detection of H1N1 nucleoprotein molecules. 87 In their work, the MNPs are anchored with polyclonal IgG antibodies specific to H1N1 nucleoprotein. Each H1N1 nucleoprotein molecule has many epitopes serving as binding sites for IgG polyclonal antibodies.…”
Section: Mps Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…This principle was used for quantitatively detecting H1N1 nucleoprotein of Influenza A Virus (IAV) subtype H1N1. The authors [ 125 ] anchored IgG polyclonal antibodies onto SPIONs surfaces. The H1N1 nucleoprotein, which hosts multiple different epitopes for these IgG polyclonal antibodies, are able to cross-link between SPIONs (IgG from the particle surface) and H1N1 nucleoproteins, forming different degrees of SPIONs clusters, depending on the number/concentration of H1N1 nucleoprotein molecules in the magnetic nanoparticle ferrofluid.…”
Section: Superparamagnetic Iron Oxide Nanoparticles Applicationsmentioning
confidence: 99%
“…The LoD was 4.7 μg mL −1 . Recently, Wu et al developed a wash-free assay based on magnetic particle spectroscopy (MPS) and the selfassembly of magnetic NP to quantitatively detect H1N1 NuP [23,24]. This rapid protocol reached the LoD of 0.25 μg mL −1 for NuP and 250 TCID 50 mL −1 for Influenza A virus.…”
Section: Introductionmentioning
confidence: 99%